2006
DOI: 10.1080/05698190500544619
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanisms of the Reduction in EHL Traction at Low Temperature

Abstract: Various experiments have revealed a dramatic traction reduction in elastohydrodynamic lubrication (EHL) contacts under subambient temperatures or with fluids of high viscosity and high pressure-viscosity coefficients. This paper conducts a systematic theoretical analysis to identify and analyze the mechanisms of this reduction. A thermal EHL model is used for the analysis that is capable of capturing many possible effects, including a thermally induced cross-film shear localization within the EHL film. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Furthermore, recent research has revealed the development of thermally induced shear localization across the EHL film under certain conditions [21,22]. The shear localization can dramatically reduce the EHL traction and may also reverse the trend of traction behavior with temperature as shown in Willermet et al [23], Webster et al [24] and Chang et al [21]. Therefore, Eq.…”
Section: Modelingmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, recent research has revealed the development of thermally induced shear localization across the EHL film under certain conditions [21,22]. The shear localization can dramatically reduce the EHL traction and may also reverse the trend of traction behavior with temperature as shown in Willermet et al [23], Webster et al [24] and Chang et al [21]. Therefore, Eq.…”
Section: Modelingmentioning
confidence: 92%
“…Because the lubricant viscosity is exponentially related to temperature, it can be very difficult to devise a close-form formula to calculate thermal EHL traction with consistent quality under various speed-andload conditions, as shown in Dama and Chang [18]. Furthermore, recent research has revealed the development of thermally induced shear localization across the EHL film under certain conditions [21,22]. The shear localization can dramatically reduce the EHL traction and may also reverse the trend of traction behavior with temperature as shown in Willermet et al [23], Webster et al [24] and Chang et al [21].…”
Section: Modelingmentioning
confidence: 97%
“…14 at ue=0.15 m/s, as well as the local increase in the central film thickness for S=-1.8 shown in Fig.15, indicate the first stages in the development of a dimple. Besides, the local increase in the central film thickness might also reduce the effect of shearing [17]. The measurement of the temperature directly inside the contact was unfortunately not possible in this study.…”
Section: Friction Coefficientmentioning
confidence: 97%
“…It leads to a number of unusual EHL behaviours including generation of sizeable dimples in the central EHL region 1,2 and dramatic reduction of EHL traction. [3][4][5] Chang carries out a parametric analysis, which suggests that the shear localisation is largely characterised by a single dimensionless parameter: 6…”
mentioning
confidence: 99%